Citizenship in a multicultural space – educational and socialization references - Szerląg, Alicja (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
Contemporary multiculturalism is dynamised by the phenomena and processes generating (un)favourable conditions for its manifestations, and for the functioning of culturally diverse societies within. It is particularly related to the disintegration of multinational countries (states), processes of immigration and exile, as well as the expansion of terrorism and the increasing level of ethnocentrism. As a result, multiculturalism has become a source of arising problems and dilemmas. The latter are accompanied by the deficit of the sense of citizenship, especially amongst the representatives of national or ethnic minorities. Yet, citizenship favours the process of establishing civic society, where concurrence of various national, ethnic, and religious groups is possible, hence the coexistence of diverse cultures is possible too, empowering the process of enriching own cultures with the values of the other cultures.
Keywords: citizenship; civic education; deficit of citizenship; family; multiculturalism; socialization